2014
DOI: 10.1539/joh.13-0236-oa
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Genotoxicity of 1,2‐Dichloropropane and Dichloromethane after Individual and Co‐exposure by Inhalation in Mice

Abstract: 205Tetsuya SUZUKI, et al.: Genotoxicity of 1,2-dichloropropane and Dichloromethane effects were greatly enhanced by simultaneous exposure to DCM. (J Occup Health 2014; 56: 205-214) Key words: 1,2-Dichloropropane, Co-exposure, Dichloromethane, Genotoxicity, InhalationRecently, the occurrence of cholangiocarcinoma cases was reported among the employees and former employees of an offset printing company in Osaka, Japan 1) . So far, 11 cancer patients have been diagnosed among 62 workers conducting offset colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Therefore, at higher concentrations, the CYP pathway becomes saturated, and the GST pathway begins to become predominant in 1,2‐DCP metabolism, possibly involving the production of a reactive episulfonium ion, which may form DNA adducts and induce genotoxicity (Kim & Guengerich, ; Zoetemelk et al ., ). From the results of a previous report, simultaneous exposure to 1,2‐DCP and DCM results in saturation of the CYP pathway, and the GST pathway begins to become the predominant metabolic route, suggesting that the genotoxicity of 1,2‐DCP is enhanced by DCM (Suzuki et al ., ). In the present study, the gene and protein expression levels of CYP2E1 and GSTT1 were not affected by exposure to the test chemicals, suggesting that the CYP pathway was not saturated and that the GST pathway did not begin to become predominant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, at higher concentrations, the CYP pathway becomes saturated, and the GST pathway begins to become predominant in 1,2‐DCP metabolism, possibly involving the production of a reactive episulfonium ion, which may form DNA adducts and induce genotoxicity (Kim & Guengerich, ; Zoetemelk et al ., ). From the results of a previous report, simultaneous exposure to 1,2‐DCP and DCM results in saturation of the CYP pathway, and the GST pathway begins to become the predominant metabolic route, suggesting that the genotoxicity of 1,2‐DCP is enhanced by DCM (Suzuki et al ., ). In the present study, the gene and protein expression levels of CYP2E1 and GSTT1 were not affected by exposure to the test chemicals, suggesting that the CYP pathway was not saturated and that the GST pathway did not begin to become predominant.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, significant increases in the frequencies of sister chromatid exchange and chromosome aberrations have been observed in the lungs, peripheral blood lymphocytes and bone marrow cells of B6C3F1 male mice that inhaled DCM (Allen et al ., ). In studies examining the in vivo genotoxic effects of 1,2‐DCP, inhalation of 1,2‐DCP but not DCM was shown to increase DNA damage measured by comet assays in the livers of C57BL/6 J mice bearing a reporter gene; furthermore, co‐exposure by inhalation of 1,2‐DCP and DCM was shown to increase the mutation frequency (MF) of the reporter gene in the liver compared with that of exposure to 1,2‐DCP alone (Suzuki et al ., ). These data indicated that the genotoxic effects of 1,2‐DCP are enhanced by DCM.…”
Section: Introductionmentioning
confidence: 97%
“…The characteristic findings in patients with occupational cholangiocarcinoma include regional dilatation of the intrahepatic bile ducts related to chronic bile duct injury, precancerous lesions including biliary intraepithelial neoplasia, and early cancerous lesions (Kaneko et al, 2014;Sato et al, 2014;Suzuki et al, 2014;Tomimaru et al, 2015). In contrast, regional dilatation of the intrahepatic bile ducts was not observed by diagnostic imaging in the sporadic group.…”
Section: Discussionmentioning
confidence: 99%
“…DCP from this bolus is being constantly eliminated from the rat's body by metabolism and excre- tion. After the Cmax, the higher concentrations of DCP in the liver and kidney could affect elimination of DCP by metabolism (Timchalk et al, 1991;Hutson et al, 1971;Jones and Gibson, 1980;Bartels and Timchalk, 1990;Suzuki et al, 2014) and excretion (Timchalk et al, 1991;Hutson et al, 1971;Jones and Gibson, 1980), and DCP concentration in the lung is expected to decrease due to exhalation (Timchalk et al, 1991;Hutson et al, 1971). After Cmax, elimination of DCP from the rat's body by metabolism and excretion results in time-course changes of DCP concentration in the tissues (Figs.…”
Section: Tissue Concentrations Of Dcpmentioning
confidence: 99%